NOTES ON THE EVIDENCE FOR THE INFLUENCE OF PRONOMINAL ON NOMINAL INFLEXION IN MYCENAEN ARCHIVES (Годишен зборник на Филозофски факултет - Скопје, 2023)
The inflexion of pronouns varies in different Indo-European languages and so far, as it can be reconstructed, in the Proto-Indo-European it was different in several aspects from the inflexion of nouns and adjectives. In the course of time pronominal and nominal inflexions went through a process of mutual levelling. The analysis and comparison of the thematic and athematic nominal inflexions has shown that gendered pronouns played important role in the development of the thematic o-stem and eH2-stem substantives.The evidence of the Greek language for the relationship of pronouns and other nomina is significant and complex at the same time, bearing in mind the individual development of Greek dialects and the archaic features of the earliest Greek records found in Mycenaean archives.The aim of this paper is to re-examine the evidence for the influence of pronominal on nominal inflexion found in Mycenaean Greek documents in the light of more recent studies and discuss its relevance for the earliest history of pronouns and nouns in the Greek language and the reconstruction of Proto-Indo-European.